Back to Course

JSS2: MATHEMATICS - 2ND TERM

0% Complete
0/0 Steps
  1. Transactions in the Homes and Offices | Week 1
    8 Topics
    |
    1 Quiz
  2. Expansion and Factorization of Algebraic Expressions | Week 2
    4 Topics
    |
    1 Quiz
  3. Algebraic Expansion and Factorization of Algebraic Expression | Week 3
    4 Topics
    |
    1 Quiz
  4. Algebraic Fractions I | Week 4
    4 Topics
    |
    1 Quiz
  5. Addition and Subtraction of Algebraic Fractions | Week 5
    2 Topics
    |
    1 Quiz
  6. Solving Simple Equations | Week 6
    4 Topics
    |
    1 Quiz
  7. Linear Inequalities I | Week 7
    4 Topics
    |
    1 Quiz
  8. Linear Inequalities II | Week 8
    2 Topics
    |
    1 Quiz
  9. Quadrilaterals | Week 9
    2 Topics
    |
    1 Quiz
  10. Angles in a Polygon | Week 10
    4 Topics
    |
    1 Quiz
  11. The Cartesian Plane Co-ordinate System I | Week 11
    3 Topics
    |
    1 Quiz
  12. The Cartesian Plane Co-ordinate System II | Week 12
    1 Topic
    |
    1 Quiz
  • excellence
  • Follow

Lesson Progress
0% Complete

Topic Content:

  • Multiplying Two Brackets (Binomial Expressions)

A binomial expression contains two terms:  

\( \scriptsize \underset{(1st\: term)}{2x} \: + \: \underset{(2nd\: term)}{3y} \: \normalsize \rightarrow \: \scriptsize Binomial \: Expression \)

In multiplying two binomial expressions like (a + b) and (x + y), follow these steps, 

(a + b)  (x + y) 

Step 1: a (x + y) 

Step 2: +b (x + y) 

Step 3: Join step 1 and 2 → (a + b) (x + y) = a (x + y) + b (x + y) 

(a – b) (x – y) = a(x – y) – b(x – y) 

Example 3.1.1:

Expand and simplify the following: 

a. (4x + 1)(x + 2)
b. (3x + 2)(2x + 3) 
c. (4f – 2) (3f – 3)
d. 10(2 + x) (3 + 2x) 

Solution 

a. (x + 1)(x + 2) = x(x + 2) + 1(x + 2) 

  = x(x) + x(2) + 1(x) + 1(2) 

= x2 + 2x + x + 2 

= x2 + 3x + 2 

b. (3x + 2) (2x + 3)

= 3x(2x + 3) + 2(2x + 3) 

= 3x (2x) + 3x (3) + 2(2x) + 2(3) 

= 6x2 + 9x + 4x + 6 

= 6x2 + 13x + 6  

c. (4f – 2) (3f – 3)

= 4f(3f – 3) – 2(3f – 3) 

= 4f(3f) + 4f(-3) – 2(3f) – 2(-3) 

= 12f2 – 12f – 6f + 6 

= 12f2 – 18f + 6 

d. 10 (2 + x)(3 + 2x)

= 10[2(3 + 2x) + x(3 + 2x)] 

= 10 [2(3) +2(2x) + x(3) + x(2x)]

= 10 [6 + 4x + 3x + 2x2]

= 10 [6 + 7x + 2x2]

= 10(6) + 10(7x) + 10(2x2

= 60 + 70x + 20x2

Evaluation Questions:

Expand and simplify the following:

  1. (x – 3) (x + 4)
  2. (x + 2) (x – 2)
  3. 2 (x + 3)2
  4. y(2 + 3x)(4 + 2y) 
  5. (8x + 3) (x – 3)
  6. (7t – 4)2

Answers 

  1. x2 + x – 12
  2. x2 – 4
  3. 2x + 12x + 18
  4. 4y2 + 12xy + 8y + 6 xy2
  5. 8x2 – 21x – 9 
  6. 49t2 – 56t + 16
avataravatar